Sagas de rpgistas: um estudo junguiano acerca do encontro com o herói via Role Playing Games - Guimarães, Paula Pinheiro Varela (2010)
This study aimed to seek an understanding of the meaning of the experience of R.P.G. games the light of Jungian Theory and as a secondary objective, list the steps of the hero journey of Joseph Campbell and the reports of the study subjects about the experience of R.P.G. games and try to understand what the exercise of heroic figure and the experience of the heroic journey with R.P.G. and bring developments to the study subjects in their real lives. It was used the theoretical framework of Analytical Psychology to contemplate the goals of this research through its concepts and the possibility of symbolic analysis of the phenomenon studied. It were made twenty semi-directed, through which it is noted that the main objective of the research was related to the construction and performance of a heroic character, and even identified content related to the stages of the heroic journey developed by Joseph Campbell, which gave rise to the secondary objectives of this research. The interviews also allowed up categories of analysis, subsequently submitted to a qualitative and quantitative analysis. These were called to the adventure, head to the unknown, apprehension of new content, physical prowess and / or spiritual, the uniqueness claim, sacrifice, otherness, refusing to return and return. These categories were correlated with the following data: age, sex, religion, professional area, playing time and favorite game. Only correlation was found between stage of the heroic journey and reached game. It was concluded that each type of game favors the experience, integration and overcoming certain stage of the heroic journey, because the focuses. By choosing the experience of a heroic character and then determined type game, the subjects respond to a need for a personal development as they choose a representative character of the expansion of consciousness and ego strength, and a game that allow you a stage of the journey heroic in what they are, so that they can evolve their processes of individuation. Thus, the choice and experience of the R.P.G. game be enable a gradual move towards himself